PENGARUH NON PERFORMING LOAN DAN LOAN TO DEPOSIT RATIO SERTA NET INTEREST MARGIN TERHADAP RETURN ON ASSETS PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011-2015 - Esa Kartika Sari (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
ABSTRACTEsa Kartika Sari, 2017. The Influence of Non Performing Loan and Loan to Deposit Ratio and Net Interest Margin to the State Owned Enterprises Bank (BUMN) listed in Indonesia Stock Exchange (BEI) Period year 2011-2015 under the guidance of Mrs. Rusdiah Iskandar and Mr. Raden Prio Utomo.This research was conducted to test the effect of Non Performing Loan and Loan to Deposit Ratio and Net Interest Margin to ROA. Objects used in this study are 4 state-owned banks listed on the Indonesia Stock Exchange within a period of research for 5 years (2011-2015).Analysis in this study used multiple linear regression. Hypothesis test used t-statistic to test the regression coefficient partially with level of significane 0,05 or 5%. In addition, the model feasibility test (F test) and classic assumption test included normality test, multicollinearity test, heteroscedasticity test and autocorrelation test.Through testing it can be seen that the NPL has a significant effect on ROA, it is mean that the first hypothesis is accepted. The LDR ratio has been known to be significant, it is mean that the second hypothesis is accepted. The NIM variable has been known that the NIM has a significant effect which means the third hypothesis is accepted. The prediction ability of these three variables on ROA is 96.5%. The remaining 3.5% is influenced by factors outside the research model. Keywords : Non Performing Loan, Loan to Deposit Ratio, Net Interest Margin, Return On Assets.